Les genres récrits : chronique n° 7 - Daniel Elmiger (Glad!)
Today, so-called generically used feminine forms, i.e. the use of grammatically feminine forms to refer to women and men (or non-binary people) are sometimes used as an inclusive writing strategy. It functions in a similar way to generically used masculine forms. While the “generic masculine” is still omnipresent, the “generic feminine” is found in various contexts, for example in regulations or texts where other strategies (such as the coordination of feminine and masculine forms) are not wanted. However, this “generic” use is not the only type of genericity that exists in French: from the point of view of reference, one can also distinguish between an individualising and a generalising, reference, which can also be called “generic”.